An Analysis of the Sanad Transmission by K.H. Muhammad Arwani (1905 – 1994) and His Role in the Dissemination of Qiraat Sab’ah Knowledge in Indonesia - Nailul Ulya, Muhim; Alkaff, Syed Abdul Rahman; Anwar, Hamdani; Ulinnuha, Muhammad (QOF, 2023)
This research delves deeply into the analysis of the sanad network of K.H. Muhammad Arwani (1905-1994 AD) and his role in spreading of Qiraat Sab’ah in Indonesia. Utilizing historical methods and document analysis, this study elucidates the dissemination process of Qiraat Sab’ah knowledge propelled by the contributions of K.H. Muhammad Arwani and his sanad network. The research highlights interpersonal relationships, education, as well as social and cultural factors that facilitated the dissemination and acceptance of Qiraat Sab’ah knowledge among the Indonesian society at that time. The findings of this study provide profound insights into the intellectual legacy of K.H. Muhammad Arwani and how his sanad network played a pivotal role in enriching the tradition of Qiraat Sab’ah in Indonesia. The results of this research hold significant relevance in the context of Indonesia's scholarly history and make a significant contribution to our understanding of the role of scholars in supporting the dissemination of religious knowledge in society.